Spatial organization of the somatosensory cortex revealed by osmFISH. (November 2018) - Codeluppi, Simone; Borm, Lars; Zeisel, Amit; Manno, Gioele; Lunteren, Josina; Svensson, Camilla; Linnarsson, Sten
Abstract Global efforts to create a molecular census of the brain using single-cell transcriptomics are producing a large catalog of molecularly defined cell types. However, spatial information is lacking and new methods are needed to map a large number of cell type–specific markers simultaneously on large tissue areas. Here, we describe a cyclic single-molecule fluorescence in situ hybridization methodology and define the cellular organization of the somatosensory cortex. osmFISH applies automated cycles of single-molecule fluorescence in situ hybridization without barcoding to provide spatial gene expression in tissue sections at high sensitivity, accuracy and throughput.